2004
DOI: 10.1086/379661
|View full text |Cite
|
Sign up to set email alerts
|

The AST/RO Survey of the Galactic Center Region. I. The Inner 3 Degrees

Abstract: We present fully-sampled maps of 461 GHz CO (4-3), 807 GHz CO (7-6), and 492 GHz [CI] (3P1-3P0) emission from the inner 3 degrees of the Galactic Center region taken with the Antarctic Submillimeter Telescope and Remote Observatory (AST/RO) in 2001--2002. The data cover -1.3 < l < 2, -0.3 < b < 0.2 with 0.5 arcmin spacing, resulting in spectra in 3 transitions at over 24,000 positions on the sky. The CO (4-3) emission is found to be essentially coextensive with lower-J transitions of CO. The CO (7-6) emission … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…Indeed, Huettemeister et al (1998) found extensive SiO emission from the CMZ clouds, indicating the presence of shocks sufficiently strong to sputter dust grains to produce a significant gas-phase abundance of SiO. Molecular gas in the CMZ is not only dense, but also warm, and able to excite high-J transitions of CO, as well as a variety of high dipole-moment molecules (Martin et al, 2004).…”
Section: Lessons From the Central Molecular Zonementioning
confidence: 99%
“…Indeed, Huettemeister et al (1998) found extensive SiO emission from the CMZ clouds, indicating the presence of shocks sufficiently strong to sputter dust grains to produce a significant gas-phase abundance of SiO. Molecular gas in the CMZ is not only dense, but also warm, and able to excite high-J transitions of CO, as well as a variety of high dipole-moment molecules (Martin et al, 2004).…”
Section: Lessons From the Central Molecular Zonementioning
confidence: 99%
“…This important region of the Galaxy hosts several sources of energetic activity, and is the site of massive molecular clouds with pockets of past and present massive star formation. On a larger scale, the distribution of molecular clouds is asymmetric in the so-called "central molecular zone" showing 2/3 of the molecular gas on the positive longitude side of the Galactic center region (Bania 1977;Bally et al 1988;Oka et al 2005;Tsuboi et al 1999;Martin et al 2004;Morris & Serabyn 1996). The nature of this asymmetry in the context of gasdynamics is not understood.…”
Section: Introductionmentioning
confidence: 99%
“…Here we investigate this possibility on a local scale and examine the application of ICS in three nonthermal filaments that are detected in both radio and X-ray wavelengths. All the filaments lie in the vicinity of molecular clouds characterized by their high density ≈ 10 4 − 10 5 cm −3 and high temperature ≈ 70 K (e.g., Morris and Serabyn 1996;Martin et al 2004). …”
Section: Introductionmentioning
confidence: 99%